The corrosion and lubrication properties of 2-Mercaptobenzothiazole functionalized ionic liquids for bronze. (October 2017) - Li, Yi; Zhang, Songwei; Ding, Qi; Feng, Dapeng; Qin, Baofeng; Hu, Litian
Abstract: Aiming at a better understanding of the structure-function relationship of the molecular structure, corrosion and lubrication properties of ionic liquids (ILs), three 2-mercaptobenzothiazole functionalized ILs were synthesized and their corrosion and lubrication properties were investigated. Results of electrochemical and tribological experiments indicated that the functionalized ILs showed much lower corrosivity and better lubricity for bronze than conventional ILs [BMIM][BF4 ]. And the investigation revealed that ILs with lower corrosivity promised the better lubrication properties via reducing the severe corrosive wear. Results from the surface analysis by XPS and SEM-EDS suggested that the anti-wear and friction-reducing mechanisms of the functionalized ILs were ascribed to synergistic effect of adsorbed ILs film and tribochemical products formed on the worn surfaces. Highlights: Three MBT functionalized ILs with low corrosivity were synthesized. The corrosion properties were assessed by electrochemical measurements. MBT functionalized ILs were first reported as high-performance lubricants. ILs with lower corrosivity promise better lubrication performances in this paper.